Studi Literatur: Inventarisasi Jenis Tumbuhan Air sebagai Bioindikator Kualitas Air Sungai - Mahardika, Nabila; Amizera, Susy (Biocaster : Jurnal Kajian Biologi, 2025)
River water pollution due to domestic, industrial, and agricultural waste poses a serious threat to aquatic ecosystems and human health. One environmentally friendly approach to monitoring water quality is through the use of aquatic plants as bioindicators. This study aims to inventory the types of aquatic plants that have the potential to be bioindicators of river water quality based on their sensitivity to pollutants and their relationship to water quality. This study was conducted through a literature study by analyzing articles from the Google Scholar, DOAJ, and GARUDA databases, published between 2015-2025, totaling 52 relevant articles regarding aquatic plants as bioindicators of river water quality. Using a qualitative content analysis and descriptive synthesis approach. The results of the analysis indicate that 12 species of aquatic plants have the potential to be bioindicators of river water quality. Some prominent species include: Cyperus papyrus, Echinodorus palaefolius, Eichhornia crassipes, Hydrilla verticillata, Ipomoea aquatica, Lemna minor, Limnocharis flava, Microsorum pteropus, Nymphaea sp., Pistia stratiotes, Salvinia molesta, and Typha angustifolia. Based on their sensitivity to pollution, aquatic plants can be grouped into Eichhornia crassipes and Ipomoea aquatica (highly sensitive), Pistia stratiotes and Salvinia molesta (sensitive), Nymphaea sp. and Limnocharis flava, Lemna minor, and Cyperus papyrus (pollution-tolerant), and Hydrilla verticillata and Microsorum pteropus (highly adaptable). This research can provide an alternative for assessing water quality through aquatic plants and increase public knowledge about aquatic plant species as bioindicators.